Kajian Sanad - Muhammad Ali (AL-Fikr, 2011)
Sanad (the cain) which had been used by the prophet’s companions was the established narrative system of the prophet tradition (hadis). Even though, many muslim or non-muslim scholar feel uncertain of its reliability as a scientific methodology. So the motivating problem being discussed in this article is what are the factors that should be fulfilled in a sanad to be concepted as a part of methodological construction? By using the historical and the science of hadis, this article discovered that in the time before islam, the resource of sanad was provided by Judaism as in their book, Mishnah. Like Judaism, in the time of pre-islamic history (jahiliah), people used the sanad way to narrate their poems. After Islamic era. Sanad of hadis became more methodological than it of pre-islamic history, especially in its reliability and consistency. This theses was pointed by hadis’ researcher as “sanad is the part of the din (islam).